Experimental Study on Response of Platform Beam of High-piled Wharf under Vehicle Load - WANG Chengqiang; GU Hao; BIAN Lei; CHEN Zhonghua; SU Zhengyang; WANG Haijun; WANG Enzhun (Renmin Zhujiang)
In order to ensure the safety management and normal operation of ports and wharfs, thispaper surveys and observes the current state of pile foundation, beams, cap beams and panels ofhigh-piled wharf platform on site, measures the strain, deflection and crack width of rearplatform beam of wharf under vehicle load through field loading test, and checks whether thebending and shear bearing capacity of the rear platform beam meet the design requirements or not. Theresults show that the maximum strain, mid-span maximum deflection and crack width of the support-closer section of the rear platform beam of wharf are all within the normal range, and the securityand service ability of wharf platform structure meet the design requirements.